TALA’AH AYAT HUKUM DAN HADIST TENTANG PEREMPUAN-PEREMPUAN YANG HARAM DINIKAHI SERTA PROBLEMATIKANYA DALAM TATANAN HUKUM INDONESIA - Firmansyah, Firmansyah (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
In Islamic law, there are 16 women who cannot be married (Haram) because of the woman herself or her lineage, or relationship due to marriage with father or mother, sexual relations/or because of family reasons. Your mothers; your daughters; your sisters, your father's sisters; your mother's sisters; the daughters of your male brothers; the daughters of your sisters; your mothers who breastfed you; half-brother; your wife's mothers (in-laws); your wife's children who are in your care from the wife you have mixed with, but if you have not mixed with your wife (and you have divorced), then it is not a sin for you to marry her; (and forbidden to you) the wives of your biological children (daughters-in-law); and bringing together (in marriage) two women who are sisters, except what has happened in the past.